The Economic Potential of Wood Carving Art and Its Marketing Strategy in Sumenep - Mohammad Takdir; Maksum Maksum; Sinawar Sinawar (Institut Seni Indonesia Denpasar, 2023)
This study aims to reveal three main issues that are the focus of this research, namely (1) how is the potential of wood carving art in Karduluk village as an artistic and cultural heritage of the Sumenep Madura community, (2) how is the promotion strategy of wood carving by craftsmen, and (3) what is the role of the government area in promoting the wood carving art of Karduluk village as the center of the craft industry in Madura. This study uses qualitative research to explore the promotion strategy of Karduluk village carving as a cultural heritage of the Madurese community. Data collection techniques in the field use three techniques, namely observation, interviews, and documentation. Meanwhile, the analytical method used is deep analysis to process empirical data in the field. In conducting data analysis, the researcher carried out several stages: data reduction, presenting empirical material, and verifying. There are three main findings in this research. First, is the potential of the wood carving art in Karduluk village, namely the economic potential, the potential for carving tourism development, and the potential interest of foreign consumers. Second, promotion strategies for wood carving art are done by participating in art exhibitions, personal selling, online promotion, increasing the variety of wood carving art models, maintaining product quality standards, and mentally competing. Third, the role of the government in promoting the wood carving art of Karduluk village, namely holding an exhibition of wood carving art products, establishing Karduluk village as a carving village, providing marketing capital assistance, assisting in partnership, and facilitating business licensing.